Biodegradable polymer drug eluting stents versus durable polymer drug eluting stents for percutaneous coronary intervention. (14th October 2021) - Kheifets, M; Levi, A; Bental, T; Perl, L; Codner, P; Wittberg, G; Talmor-Barkan, Y; Landes, U; Samara, A; Greenberg, G; Erez, A; Vaknin-Assa, H; et al.
Abstract: Background: Invasive angiography with subsequent revascularization is a widely used treatment method in patients with coronary heart disease. Although biodegradable polymer drug eluting stents (BP-DES) have been used for almost a decade now, clinical trials regarding their long-term outcomes are both sparse and inconsistent. We aimed to compare the long-term outcomes of patients undergoing percutaneous coronary intervention (PCI) with BP-DES versus durable polymer drug eluting stents (DP-DES). Methods: Among 11, 517 PCIs with second generation drug eluting stents preformed in our institution between 2007 and 2019, we identified 8042 procedures performed using DP-DES and 3475 using BP-DES. The primary outcome was the composite of all-cause mortality, recurrent myocardial infarction (re-MI), target vessel revascularization (TVR) and coronary artery bypass grafting (CABG). Propensity score matching was used to create a well-balanced cohort. Results: Mean follow up was 4.8 years. Of the 3, 413 matched pairs, 21% were females, and the mean age was 66. At one year, the primary outcome occurred in 9.6% patients versus 8.3% (p=0.05), and TVR rate was 4.1% versus 3% (p=0.005) in patients with DP-DES and BP-DES respectively. Within 5 years, the primary outcome occurred in in 24.9% versus 24.8% (p=0.83), and the rate of TVR was 9.8% versus 9.1% (p=0.07) in patients with DP-DES and BP-DES respectively. Conclusions: Similar rates of the composite outcome were observed throughout the entire follow-up. TVR rates were lower in the DP-DES group at 1-year but equalized within 5 years. FUNDunding Acknowledgement: Type of funding sources: None.